(untitled) (BIRDEM Medical Journal, 2017)
A bezoar is the result of the ingestion of indigestible or poorly digestible substances that accumulate in the gastrointestinal tract in the form of a mass. Among different types of bezoars phytobezoars is the most common type and formed by excessive consumption of herbal nutrients containing high amounts of indigestible fibers. There are some predisposing factors for gastrointestinal phytobezoars formation such as loss of pyloric function, decreased gastric motility, malabsorption, inadequate chewing and excessive consumption of herbal indigestible fibers. Small bowel obstruction is the most common major complication of phytobezoars. We present a rare case of intestinal obstruction in a middle aged man who was previously diagnosed to have malabsorption and used to take herbal medicine. He was treated successfully by right hemicolectomy under general anesthesia. On histopathological examination a large phytobezoar was found in the terminal part of ileum. Birdem Med J 2017; 7(1): 64-67